A combined theoretical and experimental study on the structure, vibrational, and electronic properties of antiparkinsonian drug safinamide - Ledesma, Ana Estela (2020)
In this work, structural, electronic, topological, and electronic and vibrational spectra of antiepileptic and antiparkinsonian drug safinamide (two enantiomers and their mesylate salt) were investigated with the DFT/TD-DFT methodology in gas phase and PCM solvent model. The absorbance maximum of safinamide was found at 227 nm, and the computed maximum transition occurred at 226 nm, which was assigned to π → π* transitions due to the chromophores C=C, C=O and C=N bonds. Electrostatic potential maps of all studied molecules revealed that the C=O group of (S)-enantiomer was more nucleophilic than the remaining molecules. Topological analysis suggested that an N–H intramolecular hydrogen bond especially in solution, and the NBO study showed a clear instability and strong ionic character of the salt. The lower electrophilicity and nucleophilicity indexes for the (S)-enantiomer than for the (R)-enantiomer, the higher reactivity it shows. At the same time, it shows higher activity as inhibitor of monoamine oxidase B. The force fields and the complete assignment of the 117 vibration normal modes of the enantiomers and 144 vibration normal modes of the mesylate salt are reported. The predicted infrared, Raman, 1H-NMR, UV–visible, and ECD spectra were in reasonable agreement with the corresponding experimental ones. In addition, the interaction with monoamine oxidase was evaluated. This study provides a structural, vibrational, and electronic characterization of the drug through theoretical insights that will contribute to further research of the biological interaction mechanism.